The impact of trauma and blood loss on human decomposition. Issue 3 (May 2019) - Cockle, Diane L.; Bell, Lynne S.
Highlights: Bloodloss was demonstrated to have a negative impact on the progression of decomposition. Sharp force trauma saw the highest volumes of bloodloss compared to ballistic and blunt force trauma. Victims of homicide in Canada were likely to be between 10 and 30 years of age.